Load Frequency Control in Four Area Power Systems Using Fuzzy Logic PI Controller - Ch. Varaha Narasimha Raja (Bulletin of Electrical Engineering and Informatics, 2013)
This paper presents a load frequency control in fourarea power systems using fuzzy gain scheduling of PI controlleris realized. The system simulation is realized by using Matlab/Simulink software. System dynamic performance is observed forconventional PI, fuzzy PI and fuzzy logic controllers.